Synthetic simulation of streamflow and rainfall data using disaggregation models - Ismail, Nurul Adzura; Harun, Sobri; Yusop, Zulkifli (Faculty of Civil Engineering, UTM, 2004)
Synthetic hydrological series is useful for evaluating water supply management decision and reservoir design. This paper examines stochastic disaggregation models that are capable of reproducing statistical characteristics especially mean and standard deviation of historical data series. Simulation was carried out on both transformed and untransformed streamflow and rainfall series of Sungai Muar. The Synthetic Streamflow Generation Software Package (SPIGOT) model was found to be the most robust for streamflow simulation. On the other hand, the Valencia-Schaake (VLSH) model is more superior for generating rainfall series.